World Development Report 1984 - World Bank, Washington, DC.; World Bank, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1984)
This report, seventh in a series of annual publications, examines the relationship between population change and development, showing why continuing rapid population growth in developing countries is likely to mean a lower quality of life for millions of people. The first part of the report concludes that the economies of developing countries can grow by more than 5 percent a year, but whether this growth is achieved depends on policy makers in both developing and developed nations. The second part examines population change and contends that many developing countries will escape from poverty only if they manage to decrease their population growth. Public policies to reduce fertility that are humane and affordable and that complement other development efforts are outlined, with special emphasis on education for women and increased family planning services. Underlying causes of the world 1980-83 economic recession are analyzed and population policy successes over the last decade are highlighted. In reviewing prospects for the next decade, the report concludes that sustained recovery requires economic reforms in developed and developing countries alike, as well as concerted international action to roll back protectionism and increase capital flows. A population data supplement and maps and graphics supplement the text. The final portion of the report comprises 28 two-page tables containing economic and social profiles of 126 countries. (LH)
Availability: World Bank, 1818 H St., N.W., Washington, DC 20433 ($8.00).
ERIC Note: For 1980 report, see ED 204 099. Insets and charts printed on colored paper may not reproduce clearly.
Microfiche.
Keywords: Birth Rate; Developing Nations; Economic Development; Family Planning; Foreign Policy; Global Approach; Human Geography; International Relations; Overpopulation; Population Distribution; Population Growth; Poverty; Quality of Life; World Problems; Reports, Descriptive